PROMOTING ENGLISH LEARNING FOR ADULT STARTERS: A GAP BETWEEN EMOTION AND TEACHING STRATEGY - Wardana I Ketut; Sri Astuti Putu (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2021)
The investigation that focuses on English language learning by adult starters at the workplace is very much challenging. Thus, this study attempted to elaborate whether emotion (self-confidence, motivation, or anxiety) correlates with teaching strategy (CBI, CLT, and TBLT) and English language performance. This study applied a combination of qualitative with phenomenology design and quantitative with analytic descriptive design to analyze the effect of emotion on teaching strategy. The population was 355 employees whose ages range from 25 to 30. this study involved 100 samples using a random sampling technique. The questionnaire consisted of 15 questions concerning self-confidence, 15 questionnaires about motivation, and 15 questionnaires about anxiety. A performance test measured the student’s language competence. The data were analyzed by descriptive statistics with SPSS 25, t-test, and Pearson Product Moment. The finding revealed that the emotion correlates positively either with the teaching strategy or with the learning achievement. The stronger the adult learners feel self-confidence and emotion, and less anxiety the more effective the CBI, CLT, TBLT can encourage their language performance. The factors that make emotion correlate more positively with language performance are (1) the demands of better achievements, (2) self-responsibility, and (3) teaching strategy.